Ethylene Polymerization‐Induced Self‐Assembly (PISA) of Poly(ethylene oxide)‐block‐polyethylene Copolymers via RAFT. (14th April 2020) - Bergerbit, Cédric; Baffie, Florian; Wolpers, Arne; Dugas, Pierre‐Yves; Boyron, Olivier; Taam, Manel; Lansalot, Muriel; Monteil, Vincent; D'Agosto, Franck
Abstract: Poly(ethylene oxide) (PEO) with dithiocarbamate chain ends (PEO–SC(=S)−N(CH3 )Ph and PEO–SC(=S)−NPh2, named PEO‐1 and PEO‐2, respectively) were used as macromolecular chain‐transfer agents (macro‐CTAs) to mediate the reversible addition–fragmentation chain transfer (RAFT) polymerization of ethylene in dimethyl carbonate (DMC) under relatively mild conditions (80 °C, 80 bar). While only a slow consumption of PEO‐1 was observed, the rapid consumption of PEO‐2 led to a clean chain extension and the formation of a polyethylene (PE) segment. Upon polymerization, the resulting block copolymers PEO‐b‐PE self‐assembled into nanometric objects according to a polymerization‐induced self‐assembly (PISA). Abstract : PEO‐ b ‐PE block copolymers were formed by reversible addition–fragmentation chain transfer (RAFT) of ethylene. The ethylene polymerization‐induced self‐assembly (PISA) of the resulting block copolymers was achieved and morphologies including spheres, worms, and 2D platelets were obtained.